Development of Organizational Commitment Analysis Structural Equation Model for Makassar Industrial Estate Employees - Tawil, Muhammad Risal (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study discusses how a measuring tool of organizational commitment was developed through confirmatory factor analysis using a tool analysis structural equation model. This study was intended to achieve the validity and reliability of the organizational commitment that met the statistical requirements. This study also conducted a model test to obtain model fit from the results of confirmatory factor analysis constructs organizational commitment. The research was conducted by using a survey using a questionnaire from Google Forms which was distributed for 2 (two) months with a sample of 251 employees of the Makassar industrial area. The results showed that of the 5 dimensions and 25 indicators of organizational commitment, all of them showed a validity value above 0.5, thus fulfilling the cut off of the required value. The results of the reliability test of the dimensions and indicators of organizational commitment also show the cut off required statistical >0.7. Apart from that, the indices of the model test results carried out are stated to have met the criteria of a good model.